Investigation of Rheological Characteristics and Bleeding Behavior of PPA-Modified Bitumen Emulsion for Microsurfacing - Mohammadjavad AkhavanBahabadi; Mohammad Khabiri (Journal of Rehabilitation in Civil Engineering)
The widespread application of bitumen emulsion, especially in surface treatment as the commonest approach to road maintenance in the world, indicates the necessity of finding ways to improve the bitumen emulsion performance. The present research is aimed at investigating the effect of polyphosphoric acid (PPA), as an admixture, on rheological characteristics of the bitumen emulsion. For this purpose, PPA was used at different dosages (i.e., 0.4, 0.8, 1.2, and 1.6 wt.% by weight of the residual bitumen emulsion) to modify the bitumen emulsion. Evaluation of the modified bitumen emulsion samples was performed based on a number of physical parameters (Saybolt Furol viscosity, softening point, penetration, and thermal sensitivity) and dynamic shear rheometer (DSR) and multiple stress creep recovery (MSCR) tests. Results of the bitumen tests showed that the use of PPA improved the bitumen emulsion characteristics in terms of reduced penetration, increased softening point, and decreased thermal sensitivity. With increasing the PPA dosage to up to 0.8 wt.% by weight of residual bitumen emulsion, the resultant changes in the penetration and softening point were significant and improved the bitumen emulsion performance. It was also observed that the value of G*/sin ( ), as a measure of resistance to bleeding in hot weather, increases with PPA dosage in all samples, with the best performance obtained with the samples containing PPA at 0.8 and 1.2 wt.%. An increase in the operating temperature of the PPA-modified samples was seen, so that the sample containing PPA at 0.8 wt.% exhibited 28.6% higher operating temperature than the control sample. The values of R% and %Rdiff parameters increased with the PPA dosage. The observed reduction of percent recovery due to increased temperature in the modified sample indicated the lower sensitivity of the modified bitumen emulsion to temperature rise. The value of Jnr parameter decreased with increasing the PPA dosage, indicating a boost in the resistance of the bitumen emulsion to bleeding.